Embarazo en adolescentes y su relación con el Tipo de parto en el Hospital Santa Gema de Yurimaguas. Julio- Diciembre 2013 - Vela Cárdenas, Gaby Makelly (2014)
The present investigation Teen Pregnancy and its relation to the mode of delivery At the Santa Gema in Yurimaguas Hospital. July-December 2013 was to determine The relationship between teen pregnancy and type of delivery. Quantitative, Descriptive, correlational, retrospective, analytical and cross-sectional study with Data collection. The population was comprised of 100 pregnant adolescents seen At the outpatient clinic of Obstetrics. Obtained by probability sampling. The Technical report was self-administered, and the instruments were the questionnaire On type of pregnancy and delivery rates. Data were analyzed using the SPSS Version 19.0 package. The statistical test used for the testing of the hypothesis was Chi-Square, with α = 0.05 with a confidence level of 95%. It was found that 77% of pregnant adolescents are aged 16 to 19 years. According To type of birth and length of gestation found that 75%, have given birth at term. According to type of delivery: Top childbirth, 93% have had spontaneous labor; Setting the chi-square test is equal to 0.320; one degree of freedom; and Significance level of 0.572 was found that there is no significant relationship Between teenage pregnancy and mode of delivery gestational age at the Santa Gema in Yurimaguas Hospital. July to December 2013. By setting the values for the Research Hypothesis Testing for Type Calving:Finalization and gestational age was obtained: The chi-square test is equal to 0.320; with one degree of freedom; and significance level of 0.572; and for Research Hypothesis Testing for Type Calving: start, end birth and gestational age Was obtained: The chi-square test is 0.323; with one degree of freedom; and Significance level = 0.570 respectively. These results determine that there is no Significant relationship between age Pregnancy and Childbirth type.